Putting the periodicity back into the periodic leg movement index: an alternative data-driven algorithm for the computation of this index during sleep and wakefulness - Ferri, Raffaele; Rundo, Francesco; Zucconi, Marco; Manconi, Mauro; Aricò, Debora; Bruni, Oliviero; Ferini-Strambi, Luigi; Fulda, Stephany (Sleep medicine, 2015)
•High periodic leg movement (PLM) indices were found in people with many leg movements, even in the absence of periodicity.•The Periodicity Index rather than the PLM index is more specific for restless legs syndrome.•An alternative PLM index calculation is proposed that takes into account this periodicity. To evaluate an alternative index for periodic leg movements during sleep (PLMS) and wakefulness (PLMW) expected to be similar to the standard index when leg movement activity is genuinely periodic, but significantly lower when periodicity is low. One-hundred-and-seven subjects with restless legs syndrome (RLS) were retrospectively identified and included (47 males, 60 females, mean age 56.9 years), along with 63 controls (33 males, 30 females, 42.2 years). Night-to-night variability was analysed in a subgroup of 17 subjects with RLS. PLMW were evaluated in a subgroup of 66 RLS subjects. Two ‘alternative’ PLMS/PLMW indices were calculated: one increased the lower limit of the inter-movement intervals from 5 to 10 s (‘Alt1’) and another additionally considered only series not interrupted by LMs with a short inter-movement interval (‘Alt2’). Despite a high correlation between methods, only the Alt2 algorithm provided significantly different results, with PLMS/PLMW indices being consistently lower than those provided by the other two methods. The difference was more evident in the controls and during wakefulness, when periodicity was lower. The difference between the Alt2 and the standard PLMS index showed a significantly negative correlation with the Periodicity Index. Night-to-night variability was similar for all PLMS indices and significantly higher than the variability seen in the Periodicity Index. This methodological study introduces an alternative to the standard PLMS/PLMW indices, initiating the validation process for a new way of computing the PLMS/PLMW index, more adherent to the parameters that allows a reliable evaluation of their periodicity.